Solution photo-copolymerization of acrylic acid and itaconic acid: The effect of polymerization parameters on mechanical properties of glass ionomer cements. (February 2022) - Balilvand, Rezvan; Nodehi, Azizollah; Keyvan Rad, Jaber; Atai, Mohammad
Abstract: Objective: To synthesize a series of poly (acrylic acid- co -itaconic acid) (P(AA- co -IA)) copolymers with different molecular weights (MWs) through a facile water-based solution photopolymerization and to investigate the operational and mechanical properties of the experimental glass-ionomer (GI) cements made of the ionomers. Methods: Thioglycolic acid (TGA) was used as a chain transfer agent to synthesize P(AA-co-IA) ionomers with different MWs through the solution photopolymerization. The chemical structure, MWs, and rheological properties of the copolymers were fully characterized. The GI cements were prepared using the ionomer solutions in different MWs and concentrations. Finally, the operating and mechanical properties of the experimental GI cements were investigated and compared with those of a commercially available GI cement. Results: The synthesis and composition of the P(AA-co-IA) were approved by spectroscopy analyses. The results revealed that by increasing the TGA content, MW and polydispersity index (PDI) of the synthesized copolymers demonstrate a decreasing trend from 4.5 × 104 g/mol (PDI of 2.45) to 7.4 × 103 g/mol (PDI of 1.62). Accordingly, the viscosity of copolymers decreased with increasing the TGA concentration in the polymerization recipes. Setting times of the cements increased with reducing the MWs and ionomer concentration. The compressive and flexural strengths of GI cements were improved by increasing the MWs, ionomers concentration, and storage time. Significance: The solution photopolymerization provides a facile and environmentally safe method to synthesize P(AA-co-IA) copolymers with controlled MWs. The structure-property relationships presented in the study also provide valuable information in the production and improvement of the GI cements. Graphical abstract: Image 1 Highlights: Photopolymerization of acrylic acid/Itaconic acid was performed in aqueous media. The polymer MW was controlled using thioglycolic acid as chain transfer agent. The polymer MW affects setting time and mechanical properties of glass ionomer.